Household Challenges, Family Dynamism and Online Learning under COVID-19 Pandemic in a South African University - Bongani innocent Dlamini; Peggy Pinky Mthalane; Albert Tchey Agbenyegah (LPPM of NAROTAMA UNIVERSITY, 2021)
Purpose: Reduce the spread of the virus amongst people, especially students and lecturers, thus online learning was introduced in 2020. To find out the effectiveness of online learning and family dynamics posed by this phenomenon. Design/methodology/approach: The researchers conducted a research at one of the University of Technology in South Africa, situated in the Province of Kwa-Zulu Natal, in Piet ermaritzburg. The main aim was to determine the challenges posed by online learning while students were at home, compounded by COVID-19 pandemic. Findings: The results of the analysis show ed the connection between family dynamics such as family settings, online learning and the impact of COVID-19 pandemic in this regard. It can then be concluded that there is a significant influence between family setting, such as bereavement, divorce, lack of internet connection and overcrowding at home, COVID-19 and the adjustment to online learning. Research limitations/implications: Lack of internet connection and overcrowding at home,COVID-19 and the adjustment to online learning. Paper type: Research paper.